A note on the time complexity of machine scheduling with DeJong's learning effect. (October 2017) - Zhao, Chuanli; Fang, Ji; Cheng, T.C.E.; Ji, Min
Highlights: This note improves time complexity of two FPTASes provided in two papers published in CAIE . Further general comments are also proposed in the last. Abstract: In a recent paper (Ji et al., 2015), the authors provided a fully polynomial-time approximation scheme (FPTAS) for the considered NP -hard problem. Extending this research, the authors in another paper (Ji et al., 2016) gave an FPTAS for a related NP -hard problem. In this note we show that the time complexity of the two FPTASes can be improved.